2004
DOI: 10.1079/phn2004632
|View full text |Cite
|
Sign up to set email alerts
|

Do childhood growth indicators in developing countries cluster? Implications for intervention strategies

Abstract: Objective: The effectiveness of geographic targeting in nutrition programmes depends largely on the degree to which malnutrition clusters within particular areas. This study investigates the extent to which the childhood nutrition indicators, stunting (heightfor-age Z-score ,22) and wasting (weight-for-height Z-score ,22), are spatially clustered; this information is used to determine the implications of spatial clustering for the effectiveness of geographic targeting. Design: Analysis of data from Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 14 publications
1
35
0
2
Order By: Relevance
“…Our study builds upon the findings on the spatial structuring of undernutrition measured by anthropometric indices on different scales, including the household and community level (17)(18)(19) . Little area-level clustering of undernutrition among children under 5 years has been reported elsewhere (20,21) . Based on these findings, some hypothesized that the basis for the differences in nutritional status within a country is determined entirely by individual-or householdlevel characteristics (21) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our study builds upon the findings on the spatial structuring of undernutrition measured by anthropometric indices on different scales, including the household and community level (17)(18)(19) . Little area-level clustering of undernutrition among children under 5 years has been reported elsewhere (20,21) . Based on these findings, some hypothesized that the basis for the differences in nutritional status within a country is determined entirely by individual-or householdlevel characteristics (21) .…”
Section: Discussionmentioning
confidence: 92%
“…Some indicated that the distribution of undernutrition is heterogeneous within a geographic area, varies between villages and households (17) and is spatially structured (18,19) . Others argued against the evidence for clustering at the community level (20) and identified the geographic extent of clustering only at a household or individual level (21) .In the present paper, we attempted to investigate the local spatial structure of stunting and wasting among children under the age of 5 years. More specifically, we aimed to: (i) evaluate whether undernutrition indicators (stunting and wasting) have a tendency to cluster; (ii) determine the physical location and scale of clustering; and (iii) determine the risk factors for the observed clustering.…”
mentioning
confidence: 94%
“…There are various methods available to calculate ICC for a binary outcome, as discussed by Wu et al (2012) for randomized controlled trials and Fenn et al (2004) for crosssectional survey data. The ICC estimation from the random intercept logistic method suggested by Wu et al has some limitations.…”
Section: Methodsmentioning
confidence: 99%
“…Equation 2 (Donald and Donner 1987;Fenn et al 2004) where σ 2 b is the between-cluster variance of the outcome variable. For binary outcome measures, σ π π…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation